Terror and the Costs of Crime - Gould, Eric D.
This paper argues that terrorism, beyond its immediate impact on innocent victims, also raises the costs of crime, and therefore, imposes a negative externality on potential criminals. Terrorism raises the costs of crime through two channels: (i) by increasing the presence and activity of the police force, and (ii) causing more people to stay at home rather than going out for leisure activities. Our analysis exploits a panel of 120 fatal terror attacks and all reported crimes for 17 districts throughout Israel between 2000 and 2005. After controlling for the fixed-effect of each district and for district-specific time trends, we show that terror attacks reduce property crimes such as burglary, auto-theft, and thefts-from-cars. Terror also reduces assaults and aggravated assaults which occur in private homes, but increases incidents of trespassing and "disrupting the police." Taken as a whole, the results are consistent with a stronger deterrence effect produced by an increased police presence after a terror attack. A higher level of policing is likely to catch more people trespassing, and at the same time, reduce the number of property crimes. The decline in crimes committed in private houses is likely an indication that the tendency for individuals to stay home after a terror attack further increases the costs of crime.terror, police, crime